Preface "Climate change: from the geological past to the uncertain future – a symposium honouring André Berger" - J. Guiot; Z. Guo; G. Ganssen; M. Claussen; M. Crucifix; T. Kiefer; M.-F. Loutre; D.-D. Rousseau; E. Wolff (Climate of the Past, 2009)
No abstract available.